A Unique Report: Development of Super Anti-Human IgG Monoclone with Optical Density Over Than 3 - Leili Aghebati Maleki; Behzad Baradaran; Jalal Abdolalizadeh; Fatemeh Ezzatifar; Jafar Majidi (Tabriz University of Medical Sciences, 2013)
Purpose: Monoclonal antibodies and related conjugates are key reagents used in biomedical researches as well as, in treatment, purification and diagnosis of infectious and non- infectious diseases. Methods: Balb/c mice were immunized with purified human IgG. Spleen cells of the most immune mouse were fused with SP2/0 in the presence of Poly Ethylene Glycol (PEG). Supernatant of hybridoma cells was screened for detection of antibody by ELISA. Then, the sample was assessed for cross-reactivity with IgM & IgA by ELISA and confirmed by immunoblotting. The subclasses of the selected mAbs were determined. The best clone was injected intraperitoneally to some pristane-injected mice. Anti-IgG mAb was purified from the animals' ascitic fluid by Ion exchange chromatography and then, mAb was conjugated with HRP. Results: In the present study, over than 50 clones were obtained that 1 clone had optical density over than 3. We named this clone as supermonoclone which was selected for limiting dilution. The result of the immunoblotting, showed sharp band in IgG position and did not show any band in IgM&IgA position. Conclusion: Based on the findings of this study, the conjugated monoclonal antibody could have application in diagnosis of infectious diseases like Toxoplasmosis, Rubella and IgG class of other infectious and non- infectious diseases.